A Fluorescent Alcohol Biosensor Using a Simple microPAD Based Detection Scheme - Thungon, Phurpa Dema; Wang, Hui; Vagin, Sergei I.; Dyck, Colin Van; Goswami, Pranab; Rieger, B.; Meldrum, Alkiviathes (Frontiers in Sensors, 2022)
A paper-based microfluidic detection device for the detection of ethanol is demonstrated in this work. The method is based on a fluorophore consisting of short-chain conjugated molecular unit susceptible to the protonation of its terminal pyridine groups, along with a carboxyl-functionalized sidechain that acts as a binder and renders it water-soluble. The resulting fluorescent paper device yields large fluorescence changes when exposed to reactions that yield H2O2 in aqueous solutions. Using an enzyme-catalyzed rection that produces H2O2 from ethanol, we developed a two-zone, cut-out paper device containing a reaction zone in which the ethanol-containing analyte is placed, and an adjacent sensor zone where we observe a fluorescence color shift proportional to the ethanol concentration. The limit of detection of the fluidic ethanol biosensor was 0.05 v/v% and the dynamic range was 0.05 – 2 v/v%. This method was employed to detect the alcohol concentration of consumer vodkas using only a paper sensor and a smartphone camera.